The pros and cons of follicular unit extraction (FUE) versus elliptical donor harvesting (FUT). (17th November 2022) - Memon, Rohail; Avram, Marc
ABSTRACT: Hair transplantation has evolved as a practice since the 1960ʹs with advances in technology and surgical technique. With various surgical techniques in existence, patients and practitioners have an abundance of options to curate the best results for the patient. However, with many options come various benefits and consequences that must be examined on a patient-by-patient basis. This review article sought to examine the various surgical modalities of hair transplantation, to outline the pros and cons of various techniques, and to help outline considerations when choosing a given surgical technique.